2019
DOI: 10.1111/fwb.13311
|View full text |Cite
|
Sign up to set email alerts
|

Macrophytes moderate the taxonomic and functional composition of phytoplankton assemblages during a nutrient loading experiment

Abstract: Ponds and shallow lakes are sensitive to eutrophication, which often increases turbidity and produces toxic algal blooms. Previous research has found that the presence of macrophytes in shallow water bodies can mitigate the effects of nutrient loading by promoting water clarity and inhibiting phytoplankton growth. However, there is still little known about how macrophyte abundance modifies the response of phytoplankton taxonomic assemblages, particularly their functional composition, to nutrient loading. We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 57 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…The submerged macrophyte H. verticillate , has been reported to produce and release allelochemicals that has inhibitory effects on Chlorella cell membrane ( Zhang et al., 2012 ) and cyanobacteria ( Wang et al., 2006 ; Gao et al., 2011 ). Over 32 days, SMs suppressed overall cyanobacteria biomass ( Table 2 ), concurring with findings from other experimental studies ( Lürling et al., 2006 ; Barrow et al., 2019 ; Amorim and Moura, 2020 ). Further, factors such as light and nutrient competition likely interacted with allelopathic controls in the mesocosms and led to the competitive exclusion of cyanobacteria.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The submerged macrophyte H. verticillate , has been reported to produce and release allelochemicals that has inhibitory effects on Chlorella cell membrane ( Zhang et al., 2012 ) and cyanobacteria ( Wang et al., 2006 ; Gao et al., 2011 ). Over 32 days, SMs suppressed overall cyanobacteria biomass ( Table 2 ), concurring with findings from other experimental studies ( Lürling et al., 2006 ; Barrow et al., 2019 ; Amorim and Moura, 2020 ). Further, factors such as light and nutrient competition likely interacted with allelopathic controls in the mesocosms and led to the competitive exclusion of cyanobacteria.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, SMs can facilitate nutrient uptake from the water column and sediment ( Sand-Jensen and Borum, 1991 ) and reduce sediment resuspension ( Horppila and Nurminen, 2003 ). Earlier studies involving small-scale experiments ( Barrow et al., 2019 ; Amorim and Moura, 2020 ) and natural aquatic ecosystems ( Chao et al., 2022 ; Peng et al., 2022 ) have repeatedly reported that the restoration of SMs decreases the phytoplankton abundance and increases water clarity. Thus, usage of SMs is a prospective tool for the elimination of algal blooms ( Jeppesen et al., 2007b ).…”
Section: Introductionmentioning
confidence: 99%
“…H. verticillata has a competitive advantage in shading, as the light crowns form rapidly. It can also reproduce readily via fragmentation and tubers, which increases its ability to uptake nutrients [38][39][40]. Thus, it can control algal biomass by limiting the external conditions required for algal growth [7].…”
Section: Synergistic Effect Of Combined Submerged Macrophyte Plantingmentioning
confidence: 99%
“…The functional phytoplankton composition based on biovolume changed more than 200 km downstream in a tropical river, suggesting that damming can filter species by their traits Graco-Roza et al (2020). An experimental study (Barrow et al, 2019) showed the influence of the macrophyte abundance in shaping phytoplankton functional diversity, based on density/biovolume; it indicated that competition for light, grazing, and probably, allelochemicals were mechanisms through which macrophytes mediated changes in the phytoplankton community. A recent experimental study accessed the relative effects of spatial overlap, grazing, and the physical environment on multiple dimensions of phytoplankton diversity (functional and taxonomical).…”
Section: Introductionmentioning
confidence: 99%